Zillennial Perceptions of Sharia Governance Implementation and Its Implications on the Reputation, Trust, and Loyalty of Islamic Banks - Maysyaroh, Siti; Rusydiana, Aam Slamet; Febriani, Dewi (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
ABSTRACT This study aims to analyze zillennial perceptions of the implementation of sharia governance and its implications for the reputation, trust and loyalty of Islamic banks. This research is quantitative research using primary data. The object of this research is zillennial customers of Bank Syariah Indonesia with a sample size of 107 respondents using purpose sampling technique. The analysis method used is Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results found that the influence of sharia governance significantly and positively contributed to improving the reputation, trust and loyalty of Islamic banks. Then, the reputation of Islamic banks increases customer trust and customer trust increases customer loyalty to Islamic banks. Finally, customer trust increases customer loyalty to Islamic banks. Therefore, it is necessary for Islamic banks to be able to implement sharia governance properly, in order to increase the reputation, trust and loyalty of Islamic banks. Future research can explore more deeply related to the variables of this study, where further research can use or add other variables that are also related and use other more comprehensive analysis methods. Keywords: Sharia Governance, Reputation, Trust, Loyalty, Islamic Banks, Zillennials     ABSTRAK                 Penelitian ini bertujuan untuk menganalisis persepsi zillenial terhadap implementasi syariah governance serta implikasinya terhadap reputasi, kepercayaan dan loyalitas bank syariah. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan data primer. Metode analisis yang digunakan adalah Structural Equation Modeling-Partial Least Squares (SEM-PLS). Hasil penelitian menemukan bahwa pengaruh sharia governance secara signifikan dan positif berkontribusi dalam meningkatkan reputasi, kepercayaan dan loyalitas bank syariah. Kemudian, reputasi bank syariah meningkatkan kepercayaan nasabah dan kepercayaan nasabah meningkatkan loyalitas nasabah terhadap bank syariah. Terakhir, kepercayaan nasabah meningkatkan loyalitas nasabah terhadap bank syariah. Maka dari itu, perlu bagi pihak Bank Syariah untuk dapat mengimplementasikan sharia governance secara baik, guna meningkatkan reputasi, kepercayaam dan loyalitas bank syariah. Penelitian selanjutnya dapat mengeksplorasi lebih dalam terkait dengan variabel penelitian ini, dimana penelitian selanjutnya dapat menggunakan atau menambahkan variabel lain yang juga berhubungan serta menggunakan metode analisis lain yang lebih komprehensif. Kata Kunci: Sharia Governance, Reputasi, Kepercayaan, loyalitas, Bank Syariah, Zillenial